(3GdeNJGQ ef cJGH GdMjhGfs - (3eLghds; (3GdLGMXs ((3CMeO Hf eMeO GHf GdLge s)
(3ChdgG (B:s
(3bGd CHh YKeGf YeQh Hf HMQ GdLGMX bGd CHh GdjbXGf SMje ai eKd gPG GdETJbGb hcGf Chd Yed hdjg GdMLGL JHGdI aSGQ EdjgG adeG bQH efgG s
(3BNQgG (B:s
(3bO cGf bhec jMSHhfc SjOkG hNGd Cfc SjO eYjhf hjbGd Gfg dfahS heG CfaSg Ci eG CTO Yjfg hbO CUGHg faSkG hYjf hGdMeO ddg QH GdYGdejf s
(3fSNI YJjbI LOkGs
(3JHUQI GdYfhGf (B:s
(3GNJjGQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG RNGQa s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs